Effect of different pozzolana on hardening process and properties of hydraulic binder based on natural anhydrite - Žvironaitė, Jadvyga; Pundienė, Ina; Gaidučis, Sergejus; Kizinievič, Viktor (Journal of Civil Engineering and Management, 2012)
The study deals with peculiarities of hydration and development of hardening structure as well as durability properties pertaining to composite anhydrite cement pozzolana binder (ACP) with different pozzolana (P). The properties of P have an effect on ACP hydration, structure development and durability properties. This effect is different than that in cement pastes. Investigations were performed with known P: natural opoka (O) and microsilica (MS), also with production waste of mineral wool – cupola dust (CD), which is famous for high fineness and amorphous structure of particles. It was established that the activity of P compounds contained in CD was very high making this waste suitable for ACP as a P component. In ACCD samples, one could observe the most intense hydration; and after a longer inductive period, the development of hardening microstructure was more rapid than in ACMS or ACO; furthermore, a remarkably higher strength was reached. The slowest hydration and structure compacting as well as the lowest strength were found in ACMS samples. It shows that the high pozzolanic activity of P is not the crucial index in evaluation of its effect on ACP properties. Chemical properties of P have a remarkably greater effect; and in case of CD, it is most likely due to reactive alkaline admixtures.